Ruminal bacterial communities differ in early-lactation dairy cows with differing risk of ruminal acidosis - Golder, Helen Marie; Rehberger, Josh; Smith, Alexandra Helena; Block, Elliot; Lean, Ian John (Frontiers in Microbiomes, 2023)
Early lactation Holstein cows (n = 261) from 32 herds in 3 regions (Australia, California, and Canada) were previously categorized using a discriminant analysis model as being high- (26.1% of cows), medium- (26.8% of cows), or low-risk (47.1% of cows) for ruminal acidosis. We aimed to investigate if (1) there would be associations between acidosis-risk groups and ruminal bacterial taxa and dietary nutrient components, (2) there would be individual or combinations of bacterial taxa that are associated with acidosis-risk groups, and (3) the abundance of bacterial taxa would be associated with intake of diet nutrient components. Diets ranged from pasture supplemented with concentrates to total mixed rations. Bacteria 16S ribosomal DNA sequences from rumen samples collected <3 h after feeding via stomach tube were analyzed to determine bacterial presence. The relative abundance of each bacterial phyla and family were center log transformed and subjected to two redundancy analysis biplots, one for acidosis-risk group and one for region. The 20 best fit families from both combined redundancy analyses totaled 29 accounting for overlapping families among analyses and were termed “influential” families. High-risk acidosis cows were associated with increased abundances of Anaerocella_f and Veillonellaceae and decreased abundances of several bacterial families with diverse characteristics. Five phyla: Firmicutes [odds ratio (OR) = 7.47±7.43], Spirochaetes (OR = 1.28±0.14), Lentisphaerae (OR = 0.70±0.07), Planctomycetes (OR = 0.70±0.09), and Tenericutes (OR = 0.44±0.15) and 9 families were associated with a higher risk of acidosis using backward stepwise elimination mixed models. Of 9 phyla identified to be of interest based on abundance and strength of association with acidosis-risk groups all had ≥1 dietary nutrient that predicted their abundance. Sugar was the most frequently associated nutrient with the 9 phyla, being in 78% (7 out of 9 phyla), crude protein in 56%, and crude fat in 44% of models. Sugar and crude protein were most associated with the influential families and all, but 3 families had ≥1 predictive nutrient for their abundance. Ruminal bacterial taxa are associated with ruminal acidosis and dietary sugar and crude protein are vital predictors of these, and thus ruminal acidosis risk.